Use of system approach in creation of educational electronic cartographic aids in Ukraine - Ostroukh Vitalii; Drohushevska Iryna (Polish Cartographical Review, 2015)
Through the example of State Scientific and Production Enterprise «Kartographia» the practical steps on publishing of educational electronic cartographic production in Ukraine are analysed. The main functions of using such products in the process of teaching as a key element of innovation techniques implementation into school education are defined. The authors represent the features of application of system approach to creation of electronic cartographic aids. The requirements to the educational electronic cartographic aids are related to the specific aspects of production tasks and technological solutions.